2015
DOI: 10.1245/s10434-015-4952-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Characteristics and Survival Outcome of Endometrial Cancer Arising in Adenomyosis: An Exploratory Analysis

Abstract: The study suggested that endometrial cancer arising in adenomyosis may be an aggressive variant of endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…Adenomyosis is a frequent finding during the histopathologic evaluation of hysterectomy specimens of patients with endometrial cancer. In previous studies, adenomyosis coexisted with endometrial cancer in 0-70% 14 of cases, which is consistent with the studies we included 6.4-66% of cases. 4,[8][9][10][11][12][15][16][17][18][21][22][23][24] Furthermore, a population-based study comprising 768 patients with adenomyosis alone exhibited a fivefold increased risk of developing endometrial cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adenomyosis is a frequent finding during the histopathologic evaluation of hysterectomy specimens of patients with endometrial cancer. In previous studies, adenomyosis coexisted with endometrial cancer in 0-70% 14 of cases, which is consistent with the studies we included 6.4-66% of cases. 4,[8][9][10][11][12][15][16][17][18][21][22][23][24] Furthermore, a population-based study comprising 768 patients with adenomyosis alone exhibited a fivefold increased risk of developing endometrial cancer.…”
Section: Discussionsupporting
confidence: 92%
“…[8][9][10][11][12] However, other studies have identified adenomyosis as the precursor of endometrial cancer. [13][14] Conversely, co-existent adenomyosis in endometrial cancer has no impact on survival outcomes according to some studies. [15][16][17][18] Nevertheless, there exists a conflict regarding the influence of adenomyosis on the prognosis of endometrial cancer, with studies reporting conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Although adenomyosis is generally considered a benign condition with no increased risk for developing cancer, the endometrial tissue within the myometrium could develop endometrioid adenocarcinoma, with potentially deep myometrial invasion [30]. Studies have reported that a history of adenomyosis significantly increased the risk of developing endometrial cancer [27,[31][32][33]. In our current study, we also found the odds of women with a history of adenomyosis were around 4 times higher among women with endometrial cancer than the controls.…”
Section: Discussionsupporting
confidence: 66%
“…In our patients, EEC-AIA was associated with significantly younger onset ages and better survival than other subtypes, as no recurrence or death occurred in EEC-AIA patients. Although EEC-AIA had similar expression of progesterone and estrogen receptors in our study, in two exploratory analyses utilizing the EEC-AIA from data in the literature and non-EEC-AIA cases from a historical cohort at the studied centers 11,14,19 , EEC-AIA patients were found to be significantly older and less likely to express the estrogen receptor. The reasons behind the differences in the clinicopathological and survival outcomes of EEC-AIA require further clarification.…”
Section: Discussionmentioning
confidence: 38%
“…Since Colman and Rosenthal firstly discovered EC-AIA in 1958 12 , only 46 and 78 cases have been reported by Machida et al 11 and Habiba et al 13 up to 2017, respectively, due to its strict definition. Available evidence for EC-AIA has been limited to case reports and exploratory analyses of the literature 14 . Due to the limited sample size and study design, no valid conclusions about the EC-AIA have been reached or generalized from these studies.…”
mentioning
confidence: 99%